Law by Decree: A critique of section 5(2) of the Income Tax Act - Cronin, Benjamin (Department of Commercial Law, 2023)
This thesis addresses the question of whether section 5(2) of the Income Tax Act 58 of 1962 (the Income Tax Act) infringes upon the Separation of Powers Doctrine and constitutes an unlawful delegation of the power to impose or reduce taxes, in terms of the Constitution. The power to determine the rate of income tax is a fiat legislative power that directly impacts upon the lives of millions of people in South Africa. This question, while one centred on the law of taxation, also implicates fundamental public law questions related to the powers of law-making by the Legislature and delegated law-making powers to the Executive. Balancing these different powers in the area of tax law has increasingly become contentious, as more powers have been delegated over the years, raising separation of powers concerns. In terms of sections 5(2)(a) and (b) of the Income Tax Act, the Minister of Finance is purportedly empowered to ‘alter' the income tax rate by virtue of the annual national budget, with effect from the ‘date or dates determined by the Minister in that announcement'. This power to ‘alter' or amend tax rates by virtue of an ‘announcement' will, in terms of section 5(2)(b) of the Income Tax Act, remain in force for a period of 12 months from the date announced ‘subject to Parliament passing legislation giving effect to that announcement'. While the unique power to raise or lower national taxes has been provided for in an Act of Parliament, the exercise of this power remains to be tested in court against the objects and language of the South African Constitution. During the course of this thesis, I will endeavour to determine whether section 5(2) of the Income Tax Act would likely survive a challenge in light of the apparent assignment of a purely legislative function to a member of the executive.